A night's tail eaudiobook - Kelly, Sofie (Magical Cats, 2019)
In the charming town of Mayville Heights, librarian Kathleen Paulson and her two cats pounce on clues to catch a killer, in the eleventh installment of this New York Times bestselling series. Spring is coming to Mayville Heights, and Kathleen's brother, Ethan, has arrived in town with his band, The Flaming Gerbils. But not everything goes as scheduled when one of Ethan's bandmates gets into a fight with a man interested in investing in the town. When the businessman's body is later found, Ethan's friend is implicated in the crime. Kathleen wants to help her brother by solving the case, but she has no shortage of suspects from which to choose. Prior to his death, the investor was fighting like cats and dogs with lots of people. If this librarian wants more than a whisker's chance of solving the case, she will need to rely on her trusty feline sidekicks, Owen and Hercules.